The Framing of Political Advocacy and Service Responses in the Crime Victim Rights Movement - Weed, Frank J. (1997)
This paper analyses two major aspects of the mobilizing frames found among local organizations in the crime victim rights movement. A national survey of 301 organizations demonstrated that organizations shape their service/action responses in terms of three conceptualizations of the victim problem. These conceptualizations clearly influence the pattern of service programs found in different types of organizations. In addition it is shown that some types of organizations are more oriented to political advocacy than others; yet all types of organizations are more apt to be involved in political action if their staff members are oriented to victim rights framed as changing the status of victims in the criminal justice system